2009
DOI: 10.1074/jbc.m901017200
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin Regulates the Association of PIPKIγ661 with the AP-2 Adaptor β2 Appendage

Abstract: The AP-2 clathrin adaptor differs fundamentally from the related AP-1, AP-3, and AP-4 sorting complexes because membrane deposition does not depend directly on an Arf family GTPase. Instead phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) appears to act as the principal compartmental cue for AP-2 placement at the plasma membrane as well as for the docking of numerous other important clathrin coat components at the nascent bud site. This PtdIns(4,5)P 2 dependence makes type I phosphatidylinositol 4-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 99 publications
0
54
0
Order By: Relevance
“…The majority of PI(4,5)P 2 in mammalian cells is synthesized by phosphorylation of phosphatidylinositol 4-phosphate (PI4P) at the 5 position of the inositol ring by one of three isoforms of type I phosphatidylinositol phosphate (PIP) kinases: a, b or c (Ishihara et al, 1996;Ishihara et al, 1998;Loijens and Anderson, 1996), and these kinases have been implicated in the generation of the pools of PI(4,5)P 2 that are responsible for clathrin-mediated endocytosis (Krauss et al, 2003;Krauss et al, 2006;Thieman et al, 2009;Wenk et al, 2001). Alternatively, PI(4,5)P 2 can also be generated by phosphorylation of phosphatidylinositol 5-phosphate (PI5P) at the 4 position by type II PIP kinases (Fruman et al, 1998;Carricaburu et al, 2003;Doughman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of PI(4,5)P 2 in mammalian cells is synthesized by phosphorylation of phosphatidylinositol 4-phosphate (PI4P) at the 5 position of the inositol ring by one of three isoforms of type I phosphatidylinositol phosphate (PIP) kinases: a, b or c (Ishihara et al, 1996;Ishihara et al, 1998;Loijens and Anderson, 1996), and these kinases have been implicated in the generation of the pools of PI(4,5)P 2 that are responsible for clathrin-mediated endocytosis (Krauss et al, 2003;Krauss et al, 2006;Thieman et al, 2009;Wenk et al, 2001). Alternatively, PI(4,5)P 2 can also be generated by phosphorylation of phosphatidylinositol 5-phosphate (PI5P) at the 4 position by type II PIP kinases (Fruman et al, 1998;Carricaburu et al, 2003;Doughman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PIPKIc isoforms are targeted to distinct subcellular sites. By regulating the dynamics of regional PI(4,5)P 2 pools, they are implicated in distinct cellular processes such as vesicular trafficking (Bairstow et al, 2006;Ling et al, 2007;Sun et al, 2013;Thapa et al, 2012;Thieman et al, 2009;Xiong et al, 2012), calcium signaling (Wang et al, 2004) or cell adhesion and migration (Di Paolo et al, 2002;El Sayegh et al, 2007;Ling et al, 2007a;Ling et al, 2002;Sun et al, 2007;Thapa et al, 2012;Thieman et al, 2009;Wang et al, 2004;Xiong et al, 2012). Moreover, PIPKIc can regulate some proteins, such as E-cadherin , by directly interacting with them.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these mice revealed a reduction in PtdIns(4,5)P 2 levels in brain accompanied by synaptic vesicle (SV) recycling defects. As PIPKIc interfaces with the clathrin-endocytosis machinery via interactions between the AP-2 adaptor complex and either the Cterminal extension present in PIPKIc_i2 (Bairstow et al, 2006;Nakano-Kobayashi et al, 2007;Thieman et al, 2009;Kahlfeldt et al, 2010) or the kinase domain (Krauss et al, 2006) we sought to confirm the findings in our PIPKIc 2/2 mouse and extend them to the PIPKIcDE17 mouse.…”
Section: Endocytosis Defects In Pipkicmentioning
confidence: 56%
“…PIPKIc_i2 was shown to be the relevant splice isoform in neurons (Nakano-Kobayashi et al, 2007) and was also shown to be an important mediator of endocytosis in MDCK and HeLa cells (Bairstow et al, 2006). Mutational and structural analysis indicates that the 26 amino acid extension of PIPKIc_i2 binds to the m2 subunit of the AP-2 adaptor complex (Bairstow et al, 2006;Kahlfeldt et al, 2010), as well as to the b2 subunit (Nakano- Kobayashi et al, 2007;Thieman et al, 2009;Kahlfeldt et al, 2010), thereby localizing PIPKIc_i2 to clathrin-coated pits. However, the kinase core domain of all PIPKIs also binds to m2, raising the possibility that other PIPKIs and splice isoforms of PIPKIc may stimulate endocytosis in some cell types (Krauss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%